2011
DOI: 10.1111/j.1472-765x.2011.03164.x
|View full text |Cite
|
Sign up to set email alerts
|

Secreted glyceraldehyde-3-phosphate dehydrogenase as a broad spectrum vaccine candidate against microbial infection in aquaculture

Abstract: Aims:  Subcellullar localizations and cross‐immunities of GAPDHs from six common pathogenic bacteria in aquaculture were investigated. Methods and Results:  Subcellullar localizations of GAPDHs of Edwardsiella tarda EIB202, Edwardsiella ictaluri ATCC33202, Aeromonas hydrophila LSA34, Vibrio anguillarum MVM425, Vibrio alginolyticus EPGS020401 and Vibrio harveyi VIB647 were analysed with Western blotting, indirect immunofluorescence and flow cytometry examinations. Immunoprotections of different recombinant GAPD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Despite the severe economic loss, no vaccination against A. hydrophila infection has been commercially applied in China [6]. The main reason for the lack of commercial vaccines might be the existence of antigenic heterogeneity of various A. hydrophila strains in the field.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the severe economic loss, no vaccination against A. hydrophila infection has been commercially applied in China [6]. The main reason for the lack of commercial vaccines might be the existence of antigenic heterogeneity of various A. hydrophila strains in the field.…”
Section: Introductionmentioning
confidence: 99%
“…piscicida. We mainly evaluated the production of antibodies at the postvaccination stage and the improvement of survival rates at a post-challenge test, which suggests that antibody production in the cobia fish species was induced by humoral or cellular immunity (Quintana & Cohen 2011;Li et al 2012). However, the mechanistic details are undergoing further studies.…”
Section: (B)mentioning
confidence: 99%
“…; Li et al . ). As an antigen, α‐enolase was reported to be expressed on the membranes of Streptococcus agalactiae (Pancholi & Fischetti ; Bergmann et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Many studies of this pathogen have already been conducted, including its taxonomy, pathogenesis, and vaccine development. In our previous studies, the housekeeping enzymes glyceraldehyde-3phosphate dehydrogenase (GAPDH) [1,2] and fructose 1,6bisphosphate aldolase (FBA) [3] in E. tarda have been shown to be secreted into the medium or localized on the surface of this pathogen, providing effective immunoprotection in the animal model of zebrafish. Many researchers have also reported that housekeeping enzymes like GAPDH and FBA perform more than one function [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%